Paciente femenino de 30 años de edad con gastritis crónica y obesidad grado 1. - Tamayo Chasin, Biuty Michell (2021)
The present theoretical-practical work details information of the clinical case of a 30-year-old female patient, single; who requests nutritional intervention due to a diagnosed clinical picture of chronic gastritis and obesity. To carry out an ideal comprehensive nutritional care plan that causes positive changes, improves symptoms and future complications in the patient with chronic gastritis and obesity. the method developed in this clinical case is descriptive, in which for a nutritional approach data of the indicators were collected anthropometric, biochemical, clinical and dietary. Regarding the nutritional status, a disorder was in the eating pattern was verified due to an inadequate dietary intake with excess of dense caloric meals, with a body mass index (BMI) of 34kg / m2, evidence of Obesity grade I with increased cardiovascular risk of ICC: 0.86cm according to relationship (waist circumference / hip circumference), This evidenced with anthropometric and dietary indicators; According to biochemical tests, the presence of leukocytosis, hypertriglyceridemia and positive for Ac is observed. Helicobacter pylori (IgG). According to the data found, it was possible to decipher the direct relationship of the current clinical picture of the patient with the pathologies already diagnosed and based on this, a follow-up was carried out for two months every twenty days to verify that the desired results symbolize us from the dietary prescription.